Inclusive Village Governance In Sirimau District, Ambon City: An Institutional And Participatory Analysis - Mike Rolobessy; Mukhlis Fataruba; Hendriyani Sigmarlatu; Farah Desi Tuasamu (Journal of Governance, 2026)
This study examines the implementation of inclusive village governance in Sirimau District, Ambon City, focusing on the participation of vulnerable groups and persons with disabilities in village planning, implementation, and oversight. Using a qualitative multi-site case study design, data were collected through in-depth interviews, participatory observation, and document analysis, guided by fifteen locally established inclusion indicators. The findings show that villages with stronger regulatory formalisation, including Village Regulations, disaggregated disability data, Inclusion Working Groups, and dedicated budget allocations, demonstrate more systematic and accountable governance capacity than villages relying primarily on customary deliberative norms. Disaggregated disability data emerge as a critical infrastructure of social inclusion because they enable needs identification, risk mapping, service targeting, and evidence-based budgeting. However, inclusive governance remains constrained by limited budgets, uneven administrative capacity, weak public awareness, and the incomplete institutionalisation of participatory mechanisms. The study argues that effective inclusive village governance in archipelagic contexts depends on the interaction between legal certainty, socio-cultural capital, data-driven planning, and multi-stakeholder coordination. Its main contribution lies in proposing a hybrid governance framework that integrates formal regulatory instruments with customary values to strengthen participation, accountability, and sustainability in village development.